2016
DOI: 10.1007/s10459-016-9681-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curriculum sample selection for medical school

Abstract: In the Netherlands, students are admitted to medical school through (1) selection, (2) direct access by high pre-university Grade Point Average (pu-GPA), (3) lottery after being rejected in the selection procedure, or (4) lottery. At Radboud University Medical Center, 2010 was the first year we selected applicants. We designed a procedure based on tasks mimicking the reality of early medical school. Applicants took an online course followed by an on-site exam, resembling courses and exams in early medical scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…The evidence for this is scarce and findings are inconclusive. Students who had not participated in selection have been found to underperform compared to students who were selected or students who had enrolled through weighted lottery after being rejected in selection (de Visser et al 2016;Schripsema et al 2014), but these findings did not always reach significance (de Visser et al 2016;Schripsema et al 2014;Urlings-Strop et al 2013). Thus, limited evidence supports the hypothesis that students who have participated in selection outperform those who have not.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The evidence for this is scarce and findings are inconclusive. Students who had not participated in selection have been found to underperform compared to students who were selected or students who had enrolled through weighted lottery after being rejected in selection (de Visser et al 2016;Schripsema et al 2014), but these findings did not always reach significance (de Visser et al 2016;Schripsema et al 2014;Urlings-Strop et al 2013). Thus, limited evidence supports the hypothesis that students who have participated in selection outperform those who have not.…”
Section: Introductionmentioning
confidence: 94%
“…Whenever performance differences are found, however small they are, applying a selection procedure seems favourable over applying weighted lottery (de Visser et al 2016;Lucieer et al 2015;Schripsema et al 2014;Urlings-Strop et al 2009. However, the differences are often not statistically significant (de Visser et al 2016;Hulsman et al 2007;Lucieer et al 2015;Schripsema et al 2014;Stegers-Jager et al 2015;Urlings-Strop et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…a videotaped lecture and reading a medical text) with first‐year GPA and concluded that these work samples could significantly better predict first‐year GPA than cognitive ability tests. In a more recent study De Visser et al showed additional value of their curriculum sample selection procedure compared with pu‐GPA, in particular for the lower pu‐GPA categories. Other recent Dutch studies also showed positive results for the use of curriculum samples for the selection of undergraduate psychology applicants .…”
Section: Non‐grades‐based Selection In the Netherlandsmentioning
confidence: 99%
“…In Europe, applicants are increasingly selected on the basis of curriculum‐sampling tests (de Visser et al., ; Häkkinen, ; Lievens & Coetsier, ; Niessen, Meijer, & Tendeiro, , ; Reibnegger et al., ; Vihavainen, Luukkainen, & Kurhila, ). These curriculum‐sampling tests are designed based on the same rationale as work‐sample tests used in personnel selection (e.g., Callinan & Robertson, ).…”
Section: A Samples Approach To Admission Testingmentioning
confidence: 99%